Nitrogen Capture The Growth of an International Industry (1900-1940) - Travis, Anthony S. (Springer International Publishing, 2018)
This monograph provides an account of how the synthetic nitrogen industry became the forerunner of the 20th-century chemical industry in Europe, the United States and Asia. Based on an earlier SpringerBrief by the same author, which focused on the period of World War I, it expands considerably on the international aspects of the development of the synthetic nitrogen industry in the decade and a half following the war, including the new technologies that rivalled the Haber-Bosch ammonia process. Travis describes the tremendous global impact of fixed nitrogen (as calcium cyanamide and ammonia), including the perceived strategic need for nitrogen (mainly for munitions), and, increasingly, its role in increasing crop yields, including in Italy under Mussolini, and in the Soviet Union under Stalin. The author also reviews the situation in Imperial Japan, including the earliest adoption of the Italian Casale ammonia process, from 1923, and the role of fixed nitrogen in the industrialization of colonial Korea from the late 1920s. Chemists, historians of science and technology, and those interested in world fertilizer production and the development of chemical industry during the first four decades of the twentieth century will find this book of considerable value. .